Treatment refusal and abandonment remain major concerns despite good outcomes with multi-modality management in pediatric medulloblastoma: Experience from a cancer center in Eastern India - Anirban Das; Rimpa Basu Achari; Lateef Zameer; Saugata Sen; Shekhar Krishnan; Arpita Bhattacharyya (Indian Journal of Medical and Paediatric Oncology)
Context: Survival in medulloblastoma, the most common pediatric brain tumor, has lagged behind in developing countries in comparison to the West. Aim: The aim of this study was to analyze the clinical profile and outcome in a cancer center in Eastern India. Methods: Twenty-nine children were retrospectively analyzed over 6 years. Results: Vomiting (79%), headache (69%), and unsteadiness (55%) were the presenting complaints. The majority (67%) had classical histology. High-risk (HR) disease (61.6%) exceeded average-risk (AR) (38.4%) disease in numbers. Treatment-refusal (27.6%) and abandonment (6.9%) were major concerns. Four-year EFS was 81% and 52%, excluding and including refusal/abandonment, respectively. There was no relapse/progression among AR patients. Four-year EFS in HR was 63%. Posterior fossa syndrome (37.5%), febrile neutropenia (29%), and ototoxicity (16.7%) were the main treatment-related morbidities. Implications: Following this audit, patient tracking to reduce abandonment, coordination to limit delay in postsurgical referral, developing strategies for molecular subgrouping, and reducing cumulative cisplatin exposure were measures adopted to improve outcome in the unit.